Indianapolis Children's Choir [v.1] - Leck, Henry; Indianapolis Children's Choir
Resumen: Presenta un concierto del Coro de Niños de Indianápolis
Contiene: Be welcome then, great sir / Henry Purcell ; arr. by Steven Richards--Svete tihiy = Gladsome light / Pavel Chesnokov--Ergen dada / arr. by Peter Lyondev--digo / Judith Shatin--Sambelele: Brazilian folk song / arr. by Eduardo Lakschevitz --Psalm of life / James Mulholland--ail away / Malcolm Dalglish--Think of me / James Mulholland
"ACDA-SP10"